EVALUASI PENERAPAN CARA PRODUKSI PANGAN YANG BAIK UNTUK INDUSTRI RUMAH TANGGA (CPPB-IRT) DI KABUPATEN KARANGANYAR - , CANDIDA ALMA PRATIWI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Food is edible materials daily to meet the needs for maintenance, growth, employment, and replacement of damaged tissue. The increase of population, technological advances, advances in education and the economy, as well as changes in the value system in society, spurring the growth of the food industry for the manufacture of processed food products as much as possible so as to meet the needs of the market. But in general it is not offset by an increase in the safety and quality of processed food itself. This study was to determine the extent berujuan Household Food Industry in Karanganyar apply CPPB-IRT in kesuluruhan aspects of production. This research is descriptive quantitative research conducted on a number of Household Food Industry is in Karanganyar to assess the application of CPPB-IRT in these industries represented by grouping these industries into the so-called Level IRTP levels, where Level IRTP consists of Level I to Level IV. Primary data were obtained by using the check list and interview directly with the responsible party knows or all activities in the industrial production, followed by direct observation of the production activity in each Household Food Industry. The results of the study of 81 IRTP spread Karanganyar indicate that as many as 53% IRTP are at Level IV